Pengaruh pemberian makanan tambahan (PMT) pada ibu hamil terhadap berat lahir bayi - Hana Shafiyyah Zulaidah; Istiti Kandarina; Mohammad Hakimi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2014)
Background: Anemia causes fetal growth disorders that affect birth weight. Antenatal care (ANC) coverage and provision of high Fe if not followed by a decrease in the incidence of anemia can result indirectly in the risk of low birth weight. Supplementary feeding is expected to resolve the issue.Objective: To assess the effect of supplementary feeding on the third trimester of pregnancy on birth weight.Method: This was a quantitative study with a study design of quasi-experiment and non-equivalent control group. The given intervention was fish-processed feeding for 30 days. The study population was pregnant women in the third trimester in all health centers in the City of Yogyakarta and the samples were 104 pregnant women in some health centers with convenience sampling technique. The subjects were divided into two, namely the treatment group (PMT) and the comparison group (non-PMT). Birth weight was weighed immediately after the baby was born. Statistical analysis used t-test and logistic regression. Results: The mean birth weight of infants in the treatment group and the comparison group was 3248 g and 2974 g, respectively, so that the difference in the mean birth weight of both groups was 274 g (p=0.0002; 95%C:131-416). Thus, supplementary feeding was shown significantly affect the birth weight. The extraneous variables that significantly influenced birth weight were pregnancy interval. Other extraneous variables were age, mid-upper-arm circumference (MUAC), education, occupation, economic status, parity, protein intake, compliance of Fe tablet intake, antenatal care, gestational age at delivery and anemia status were not proven statistically significant to affect birth weight. Conclusion: Supplementary feeding effect on birth weight.